PLANT-BASED SUPEROXIDE DISMUTASE SUPPLEMENTATION IN THE ATHLETE POPULATION - Dudašova Petrovičova, Olina; Đorđević, Brižita; Todorović, Vanja (Journal of Medical Biochemistry, 2026)
Physical exercise significantly influences the redox balance, with its intensity, duration, and type affecting the production of free radicals, including reactive oxygen and nitrogen species. An excess of free radicals can lead to oxidative stress. Elite athletes, due to rigorous training and often insufficient rest, are particularly susceptible to oxidative stress, which can negatively affect their health and sports performance. Plant-based superoxide dismutase (SOD), combined with gliadin isolated from wheat, is a relatively new dietary supplement known for its antioxidant properties. Aim of this review was to evaluate the effects of SOD/gliadin supplementation among athletes. We examined the impact of this supplementation on redox status, inflammatory markers, indicators of muscle damage, and sports performance. Overall, the analysis of the data indicated some beneficial effects on all observed aspects of athletes’ health and performance. The effects of supplementation appear to depend on the type of sport, the athlete’s training status, and the design of the supplementation study. However, very few studies have been published on this topic; therefore, further research is needed to clarify the potential benefits of SOD/gliadin supplementation for athletes. Future studies should include a larger number of participants and implement controlled conditions with standardized dosage regimens, enabling more robust, comparable, and reliable outcomes.